The level of individual participation of community in implementing effective solid waste management policies - A. Brotosusilo; S.H. Nabila; H.A. Negoro; D. Utari (Global Journal of Environmental Science and Management)
It is crucial to achieve effective solid waste management involving not only formal/government agencies, but also individual/informal/voluntary actions in order to create a healthy environment. This study conducted to unveil the factors that increase individuals’ community participation in solid waste management policy. The data were matched with a literature review on existing waste policies to identify gaps in knowledge, which could provide beneficial policy recommendations for the Jakarta Provincial Government. The ordinary least squares regression and Indonesian family life survey data were used. The respondents’ waste handling and participation scores with potentially affected variables were calculated and regressed. Out of 1.791 respondents, the regression revealed that the participation of individuals from Jakarta is influenced by 1) the frequency of their involvement in social community activities, 2) their education level, and 3) per capita expenditure. The solid waste management score increased by 0.233 if the respondents were more socially active, with a participation score of 1. Empowerment had a 0.06 coefficient correlation relative to the waste handling score. According to the broader sample of 28.967 respondents from large cities in Indonesia. It was concluded that individuals’ participation could be enhanced by hosting various social activities at the grassroots level. The study’s gaps show that the Jakarta Provincial Government has a high propensity towards increasing individuals’ participation in solid waste management by maximizing control of the factors mentioned above (especially empowerment), as well as by raising the frequency of citizens’ involvement in social community activities at the grassroots level.